The Impact of Implementation of Electronic Prescription on Patient Satisfaction in Primary Health Centers Medan - Frengki Daniel Tampubolon; Azizah Nasution; Urip Harahap (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: The digital transformation of primary care services necessitates the implementation of electronic prescriptions to optimize productivity, performance, accuracy, service quality, and patient satisfaction. Objectives: This study analyzed the impact of the quality of pharmacy care on patient satisfaction levels and identified the dimensions with the highest to the satisfaction. Methodology: The quantitative phase involved a patient survey using the Service Quality (SERVQUAL) which consits of tangible facilities, reliability, responsiveness, assurance, and empathy along with satisfaction indicators. Data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) to determine the influence of each dimension. The qualitative phase consisted of in-depth interviews with ten pharmacy personnel to clarify and enrich the quantitative findings, followed by a comprehensive integration of both datasets. Results: Most (65.8%) of the participants were female. All SERVQUAL dimensions significantly influenced patient satisfaction. Responsiveness showed the strongest contribution with an Original Sample (O) value of 0.302, followed by empathy (O = 0.254) and assurance (O = 0.185). Reliability and tangibles had a negative yet significant effect. The qualitative findings revealed that real-time prescription input accelerated service delivery. Limited human resources, inadequate infrastructure, network instability, and irregular polyclinic workflows weakened perceptions of service consistency and physical service quality. Conclusion: Patient satisfaction is primarily determined by service speed, quality of interaction, and clarity of information, as reflected in the strong dimensions of responsiveness, empathy, and assurance. The reliability and tangibles dimensions were affected by weakness of infrastructure weaknesses and workflow issues.